Malaysian SMEs Competing in Global Business: A Comparative Study - Muhammad Naqib, Mat Yunoh (2010)
The main objective of this research is to gain an understanding about the challenges faced by Malaysia Small Medium Enterprise (SMEs) when their expanding business abroad. This study is also looking at the role of government agencies in helping Malaysian SMEs to meet the global challenges. This study used qualitative research method as an approach. Two SMEs were selected namely Pemasaran Ramly Mokny Sdn Bhd (PRMSB) and Orang Kampung Holdings Sdn Bhd (OKHSB) and comparison were made on them. The results of this study found that both SMEs faced several challenges and still not fully used incentives provided by the government. Malaysian SMEs meet several challenges abroad such as recession, global sourcing, lack of government support, relationship between SMEs and multinational corporations (MNC), intellectual property issue, legal issues in global business environment, decision process and R&D in SMEs, and also branding the products in the international market. The government is devoting and designing the SME development plan to assist the SMEs to meet the business challenges in the competitive global business environment. Government also has always taking steps to encourage the creation and development of entrepreneurs by providing positive business environment, tax incentives, training programs and various financing scheme. Capacity efforts need to point on raising awareness among SMEs of the range of government services that are available. Still too many SMEs are ignorant of grants and programs and therefore do not apply all the available incentive that offers by government.